2021
DOI: 10.1155/2021/6628814
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Albendazole on Cytokine and Chemokine Response Profiles in Echinococcus multilocularis-Inoculated Mice

Abstract: Objective. Alveolar echinococcosis (AE) is a zoonosis caused by the larval stage of the metacestode Echinococcosis multilocularis with a tumor-like behavior in the targeted organ, especially in the liver. Surgery with albendazole is first-line modality for AE. Drug discontinuation is usually based upon the parasitic viability shown by the positron emission tomography (PET) scan. However, as a demanding and expensive method, it is not widely practiced in majority of the endemic regions. Further understanding on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…Treatment with ABZ caused a significant reduction in GATA3 and a non-significant reduction in GPX1 expression, which agreed to some extent with results documented by Wu et al [ 48 ] and Kim et al [ 58 ], where ABZ showed a non-significant reduction of messenger ribonucleic acid (mRNA) expressions of GATA3 transcription factor and the mRNA expression of the antioxidant enzymes catalase, GPX1, and GPX3 used in the treatment of experimental Echinococcus multilocularis and prostate cancer, respectively. This difference might be due to different drug regimens and infections.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Treatment with ABZ caused a significant reduction in GATA3 and a non-significant reduction in GPX1 expression, which agreed to some extent with results documented by Wu et al [ 48 ] and Kim et al [ 58 ], where ABZ showed a non-significant reduction of messenger ribonucleic acid (mRNA) expressions of GATA3 transcription factor and the mRNA expression of the antioxidant enzymes catalase, GPX1, and GPX3 used in the treatment of experimental Echinococcus multilocularis and prostate cancer, respectively. This difference might be due to different drug regimens and infections.…”
Section: Discussionsupporting
confidence: 92%
“…All treated groups in the present study showed a significant reduction in the level of IL-12 in comparison to the positive control group either in intestinal or muscular phases, which coincides with Abd El-Hamed et al [46], and Salama et al [47] results, where a significant reduction in serum TNF-was observed in all treated groups either with ABZ or herbal extracts at different PI periods. However, the significant reduction that occurred with ABZ either alone or loaded with NLCS did not concede with Wu et al [48], where ABZ caused a non-significant reduction of the plasma level of IL-12 (p > 0.05) in Echinococcus multilocularisinfected mice. Also, the significant reduction that occurred with MFS either alone or combined with NLCs did not concede with Palić et al [49,50], who stated that MFS in the treatment of Leishmania targeted the Th-1 signaling, increasing the concentrations of pro-inflammatory Th-1 cytokines, such as IFN-γ and IL-12 and induced a shift of the macrophage phenotype, which is essential for the clearance of intracellular pathogens which we refer to the use of different infection models.…”
Section: Discussioncontrasting
confidence: 56%
“…It has been reported that E. multilocularis infection prevents the maturation of DCs, as illustrated by the diminished expression of various costimulatory molecules and chemokine receptors (10,41). To investigate whether IDO1 is involved in the maturation of DCs in mice infected with E. multilocularis, we next evaluated its effects on the expression of multiple phenotypic maturation markers, namely CD80, CD86, MHC II, CD11b, CXCR4, and CCR7, on DCs in infected IDO1 -/and WT mice (Figure 3A).…”
Section: Deficiency Of Ido1 Signaling Results In Enhanced Maturation ...mentioning
confidence: 99%
“…However, in the present study, antigen 5 shows a similar abundance in all studied conditions, indicating that the higher ratio observed in albendazole-treated patients probably corresponds to an increase in cyst permeability rather than greater antigen production and release in either a soluble or sEV-linked manner. As we mentioned before, the increase in cyst permeability by albendazole favors the leakage of antigens that promote antibody production [ 69 ] and the pro-inflammatory response, which is beneficial for limiting parasitic progression in both CE and alveolar echinococcosis [ 25 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%